Comprehensive geriatric assessment (CGA) in perioperative care: a systematic review of a complex intervention - Robert Hinchliffe; Ronelle Mouton; Philip Braude; Rachael Lucia Miller; Jonathan David Barnes (BMJ Open, 2022)
Objectives Comprehensive geriatric assessment (CGA) is a complex intervention applied to older people with evidence of benefit in medical populations. The aim of this systematic review was to describe how CGA is applied to surgical populations in randomised controlled trials. This will provide a basis for design of future studies focused on optimising CGA as a complex intervention.Setting A systematic review of randomised controlled trials.Participants A systematic search was performed for studies of CGA in the perioperative period across Ovid MEDLINE, Ovid EMBASE, CINAHL and Cochrane CENTRAL, from inception to March 2021.Interventions Any randomised controlled trials of perioperative CGA versus ‘standard care’ were included.Outcome measures Qualitative description of CGA.Results 12 121 titles and abstracts were screened, 68 full-text articles were assessed for eligibility and 22 articles included, reporting on 13 trials. 10 trials focused on inpatients with hip fracture, with 7 of these delivering CGA on a geriatric medicine ward, 3 on a surgical ward. The remaining three trials were in elective general surgery all delivering CGA on a surgical ward. CGA components, duration of intervention and personnel delivering the intervention were highly variable across the different studies. Trials favoured postoperative delivery of CGA (11/13). Only four trials reported data on adherence to the CGA intervention.Conclusions CGA as an intervention is variably described and delivered in randomised controlled trials in the perioperative setting. The reporting of both the intervention and standard care is often poor with little focus on adherence. Future research should focus on clearly defining and standardising the intervention as well as measuring adherence within trials.PROSPERO registration number CRD42020221797.